Ehrlichia chaffeensis Tandem Repeat Proteins and Ank200 are Type 1 Secretion System Substrates Related to the Repeats-in-Toxin Exoprotein Family - Wakeel, Abdul; den Dulk-Ras, Amke; Hooykaas, Paul J.; McBride, Jere W. (Frontiers in Cellular and Infection Microbiology, 2011)
Ehrlichia chaffeensis has type 1 and 4 secretion systems (T1SS and T4SS), but the substrates have not been identified. Potential substrates include secreted tandem repeat protein (TRP) 47, TRP120, and TRP32, and the ankyrin repeat protein, Ank200, that are involved in molecular host-pathogen interactions including DNA binding and a network of protein-protein interactions with host targets associated with signaling, transcriptional regulation, vesicle trafficking and apoptosis. In this study we report that E. chaffeensis TRP47, TRP32, TRP120, Ank200 were not secreted in the Agrobacterium tumefaciens Cre recombinase reporter assay routinely used to identify T4SS substrates. In contrast, all TRPs and the Ank200 proteins were secreted by the Escherichia coli complemented with the hemolysin secretion system (T1SS), and secretion was reduced in a T1SS mutant (ΔTolC), demonstrating that these proteins are T1SS substrates. Moreover, T1SS secretion signals were identified in the C-terminal domains of the TRPs and Ank200, and a detailed bioinformatic analysis of E. chaffeensis TRPs and Ank200 revealed features consistent with those described in the repeats in toxins (RTX) family of exoproteins, including glycine- and aspartate-rich tandem repeats (TRs), homology with ATP-transporters, a noncleavable C-terminal T1SS signal, acidic pIs, and functions consistent with other T1SS substrates. Using a heterologous E. coli T1SS, this investigation has identified the first Ehrlichia T1SS substrates supporting the conclusion that the T1SS and corresponding substrates are involved in molecular host-pathogen interactions that contribute to Ehrlichia pathobiology. Further investigation of the relationship between Ehrlichia TRPs, Ank200 and the RTX exoprotein family may lead to a greater understanding of the importance of T1SS substrates and specific functions of T1SS in the pathobiology of obligately intracellular bacteria.